2014
DOI: 10.1016/j.curtheres.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Thymoquinone in a Model of Neuropathic Pain

Abstract: BackgroundThe goal of our study was to determine the therapeutic effects of thymoquinone in a dose-dependent manner in a model of neuropathic pain following an experimentally applied spinal cord injury (SCI).MethodsFifty female adult Wistar albino rats weighing between 220 and 260 g were included in the study and were divided into 5 groups as follows: Group S (sham), Group C (control), Group T100 (100 mg/kg thymoquinone), Group T200 (200 mg/kg thymoquinone), and Group T400 (400 mg/kg thymoquinone). To begin th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 27 publications
4
21
0
1
Order By: Relevance
“…Measurement of TOS may indicate the concentration of all free oxidant radicals caused by neuropathic pain‐related oxidative damage. TAS may be an important factor in providing protection from neurological damage caused by neuropathic pain‐related oxidative stress as it is difficult to measure each antioxidant separately . In the present study, TAS is elevated by UA administration in CCI rats in both spinal cord and sciatic nerve.…”
Section: Discussionmentioning
confidence: 50%
“…Measurement of TOS may indicate the concentration of all free oxidant radicals caused by neuropathic pain‐related oxidative damage. TAS may be an important factor in providing protection from neurological damage caused by neuropathic pain‐related oxidative stress as it is difficult to measure each antioxidant separately . In the present study, TAS is elevated by UA administration in CCI rats in both spinal cord and sciatic nerve.…”
Section: Discussionmentioning
confidence: 50%
“…Las modificaciones con respecto a los rangos de movimiento en pacientes con artrosis de rodilla son diferentes, sobre todo en flexión de rodilla en cada fase de la marcha, esto como mecanismo de protección contra el dolor, ya que, si la flexión aumenta, el movimiento interarticular probablemente también lo hace incrementando el roce articular y así los síntomas (9). Sin embargo, los cambios en la excursión de movimiento dependen del estadio de la enfermedad, índice de masa corporal, edad y género, según Ko los rangos de movimiento no son estadísticamente diferentes en el plano sagital en las articulaciones de rodilla, tobillo y cadera entre personas sanas y con artrosis de rodilla en sus estadios 1 y 2, esto comparando la marcha usual, la marcha rápida y después de 30 minutos (10).…”
Section: Discussionunclassified
“…x 34 x 34 cm 3 ) of the Plexiglass formalin test box in pairs for fifteen (15) minutes daily for four (4) days, and singly for three (3) days prior to the test 9,10 . On the day of experiment, the rat was intraperitoneally injected with 1% solution of Tween 20 or Nigella sativa oil 0.5 ml/kg or 1 ml/ kg or 1.5 ml/kg body weight, in accordance with the experimental paradigm being followed.…”
Section: Formalin Testmentioning
confidence: 99%
“…Previous studies demonstrated antinociceptive and anti-inflammatory effect of Nigella sativa, in animal models [12][13] . Recently, both single and long term supplementation of Nigella sativa has been demonstrated its good protective effects against nociceptive pain [14][15] .…”
mentioning
confidence: 99%